Anthropometric and physiological profiling of youth soccer goalkeepers - Rebelo-Gonçalves, R.; Coelho e Silva, M. J.; Severino, V.; Tessitore, A.; Figueiredo, A. J. (International Journal of Sports Physiology and Performance, 2015)
Studies focused on position-related characteristics of young soccer players often ignore the goalkeepers. The aim of this study was to examine the effect of playing position on anthropometry, physiological attributes, soccer skills, and goal orientation across adolescence. One hundred forty-five soccer players age 11-19 y were assessed in training experience, body size, maturation, physiological parameters, soccer skills, and goal orientation. Factorial ANOVA was used to test the effect of age group, playing position, and respective interaction terms, while analysis of variance was used to compare goalkeepers vs outfielders in middle (under 13 [U-13] and U-15) and late (U-17 and U-19) adolescence. Discriminant analysis was used to identify the variables that contributed to explaining playing positions. Age group was a consistent source of variation for all variables except task and ego orientations. Fat mass, agility, endurance, dribbling speed, shooting accuracy, and passing were affected by the gradient derived from the classification between goalkeepers and outfielders. It was possible to correctly classify the playing position based on fat-free mass and 3 manipulative skills in younger players and on 4 skills in U-17 and U-19 soccer players. Future research should include longitudinal information to improve our understanding of the factors that contribute to distinguish goalkeepers from outfielders.